Retrospective study of risk factors and the prevalence of injuries in HIFT - Teixeira, R. V.; Dantas, M.; Gama de Motas, D.; Gálvez-González, J.; Gantois, P.; Aidar, F. J.; Moreira Silva Dantas, A.; de Queiros, V. S.; de Macedo Cesário, T.; de Araújo Tinôco Cabral, B. G. (International Journal of Sports Medicine, 2000)
The aim of this study was to investigate the risk factors and the incidence of injuries in high-intensity functional training (HIFT) practitioners. A survey was administered to 213 HIFT practitioners. Participants reported the number of injuries, the location of the injuries, and training exposure during the preceding six months and answered questions regarding potential risk factors for injury. We found there were 7.1 injuries for every 1000 hours of training. In addition, we found that individuals with experience in the modality (>2 years) were 3.77 times more likely to be affected by injury when compared with beginner individuals (<6 months) (CI95%=1.59-8.92; p=0.003). When the analysis was performed only for the competitive level, we found that practitioners competing at the national level were 5.69 times more likely to experience an injury than competitors who do not compete (CI95%=1.10-29.54; p=0.038). We also found that the injuries mainly affect the shoulder and lumbar regions. It was possible to conclude that subjects with a higher level of experience in the modality are more likely to be affected by injuries and that the shoulder and lumbar areas are most likely to be injured during HIFT.